Development of integrated floating house conceptual model for flood prone area in Malaysia : NOAH project - Yau Patrick, Siaw Yang (2007)
The construction technology of integrated floating house system for flood prone area is a new idea and approach in Malaysia. Up to the present, there is still no proper design or practical concept of how beneficial is an integrated floating house during the period of flooding. The raise of the sea level due to the effect of global warming, Southwest Monsoon and Inter-Monsoon greatly increase the risk of flood for low-lying area in Malaysia. Thus, this project is an effort towards saving valuable household and human. The objective of the project is to develop an integrated floating house conceptual model with the ability to endure lateral current forces, with the specification of stability, suitable foundation, economy in costs and practicality. There are several methodologies has been carry out for this project. Observation has be done on various floating house system regardless of it purpose. The overview on the current existing floating system including the strength of the structure, materials, degree of stability, the degree of withstand the lateral forces of water current and cost of construction. Through the interview and questionnaire, the idea of floating house and the comment regarding the existing floating house was obtained from the local experts. After the investigation on the existing floating house system and the experts’ opinion, a new construction technology of floating house has been developed and tested with CSC structural analysis software and several related scientifically calculation. With the validation of local experts, the conceptual model can be use to conduct the prototype testing and real time testing. This is the new integrated floating house conceptual model with comply with the standard of floating structure, safety requirements, economical and suit to the local requirement. By this new construction technology of integrated floating house, we believe that we will be able to minimize the effects of flooding for flood prone area in Malaysia.